A numerical model for laminated composite thin-walled members with openings considering shear lag effect. (15th April 2019) - Vojnić-Purčar, M.; Prokić, A.; Bešević, M.
Highlights: A novel model describing the shear lag has been developed. Warping of open-closed cross-sections is defined by displacements parameters at selected nodes. A unique analysis of thin-walled beams composed of open and closed cross sections. Compatibility requirements are satisfied. Computing program and numerical results has been presented. First attempt to present shear lag for beams with open and closed cross-sections. Abstract: A novel model describing the shear lag of laminated composite thin-walled beams with openings has been developed. Warping of open-closed cross- sections is defined by displacements parameters at selected nodes. Vlasov's assumption of neglecting shear strains in the middle surface is not necessary and stresses can be calculated directly from the strains. The general approach to the solution of the problem is based on the finite element method and linear stiffness matrix has been derived using the principle of virtual displacements. Computing program has been developed and numerical results for thin-walled laminated beams with openings have been presented.